1/f Noise Characterization of Bilayer MoS2 Field‐Effect Transistors on Paper with Inkjet‐Printed Contacts and hBN Dielectrics. (29th May 2021) - Pimpolari, Lorenzo; Calabrese, Gabriele; Conti, Silvia; Worsley, Robyn; Majee, Subimal; Polyushkin, Dmitry K.; Paur, Matthias; Casiraghi, Cinzia; Mueller, Thomas; Iannaccone, Giuseppe; Macucci, Massimo; Fiori, Gianluca
Abstract: 1/ f noise represents the dominant source of noise in the low‐frequency range in several physical systems, including field‐effect transistors. Its investigation can provide very important information on the fabrication process, highlighting the steps that are more prone to the introduction of defects. Here, 1/ f noise in bilayer MoS2 transistors on paper with inkjet‐printed Ag contacts and hBN dielectric is investigated. These devices are promising building blocks for future low‐cost, flexible, and easily recyclable disposable electronics. The analysis of 1/ f noise, performed following Hooge's empirical approach, results in a Hooge parameter ≈1–10, which is comparable to those reported for bilayer MoS2 transistors on SiO2 . The present results indicate that the noise properties of the investigated devices are stable against substrate bending and are mainly determined by the printing of the dielectric, while not being sensibly affected by the use of the paper substrate. These results are promising for the further development of low noise 2D material‐based flexible electronics on paper. Abstract : A detailed low‐frequency noise analysis of bilayer MoS2 transistors fabricated on paper substrate with inkjet‐printed dielectrics and contacts is presented. The extracted noise figure of merit is comparable to those reported for monolayer and bilayer MoS2 transistors fabricated on SiO2 using conventional techniques. These results are promising for the future development of low noise flexible electronics based on 2D materials.